Associations Between the Choroidal Vascularity Index and Malignant Glaucoma After Trabeculectomy for Primary Angle Closure Glaucoma - Chengguo Zuo; Dingqiao Wang; Xinxing Guo; Hui Xiao; Shaoyang Zheng; Mingkai Lin; Lei Fang; Xing Liu (Frontiers in Medicine, 2021)
Purpose: To compare the choroidal vasculature characteristics by using the choroidal vascularity index (CVI) in eyes with malignant glaucoma (MG), fellow eyes with non-MG, and eyes with uncomplicated primary angle-closure glaucoma (PACG) after trabeculectomy by spectral-domain optical coherence tomography (SD-OCT).Methods: This case–control study included 53 patients diagnosed with MG after trabeculectomy. Eyes with MG (n = 53) and the fellow eyes with non-MG (n = 50) were included. Eyes with PACG without MG after trabeculectomy (n = 60) were also enrolled as controls. The choroidal parameters, including CVI and the subfoveal choroidal thickness (SFCT), were measured by using SD-OCT images.Results: Eyes with MG and the fellow eyes showed a significantly lower CVI than eyes with PACG controls (p < 0.001). After adjusting for age, sex, axial length (AL), and intraocular pressure (IOP), eyes with the greater CVI [odds ratio (OR), 0.44] were significantly related to MG. The area under the receiver operating characteristic curve of the CVI was greater than that of the SFCT in the diagnosis of MG (0.911 vs. 0.840, p = 0.034).Conclusion: Eyes with MG showed a significantly lower macular CVI than eyes with PACG controls. A higher macular CVI was an associated factor of eyes with MG. The CVI serves as a more stable and sensitive indicator for MG than the SFCT in this group of patients with PACG.